Prevalence of Overweight and Obesity and Its Association with Nutrition-related Knowledge, Attitudes and Practices (KAP) Among Malaysian Deaf Adults - Yap, Anastasia Xin Wei; You, Yee Xing; Zaman, Farisah Najwa; Azlan, Ain Nasuha; Mohd Rashid, Syar Meeze; Krishnasamy, Shanthi; M Zapawi, Muhamad Mustaqim; Suzana, Suzana (Jurnal Gizi dan Pangan, 2025)
This study examines the prevalence of overweight and obesity and determines the association between nutrition-related Knowledge, Attitudes, and Practices (KAP) and obesity among deaf adults from low-income households in Klang Valley, Malaysia. Using purposive sampling, 120 deaf adults from three community centres participated in this cross-sectional study. Anthropometric measurements and sociodemographic data were taken along with information on nutritionrelated KAP were collected via a validated questionnaire with assistance from a certified Malaysian sign language interpreter. The average age of participants was 43.1±10.5 years, with a majority being female, Malay, and educated at the secondary level. Overweight and obesity prevalence reached 58.3%. Mean scores for nutrition-related KAP were 53.1±17.5, 4.2±1.7, and 7.4±2.2, respectively. Lower scores in healthy eating practices were significantly associated with higher odds of obesity after adjusting for age, ethnicity, education years, waist-to-hip ratio and body fat percentage (OR=0.73; 95% CI: 0.55‒0.97; p<0.05). Poor eating practices are associated with obesity among deaf adults. A targeted nutrition education initiative addressing the specific needs of this population is essential to reduce obesity risks.